Applicability of Islamic microfinance as an alternative tool for Poverty Eradication in Nigeria - Abdulqadir Maikabara Abdullateef (Institut Agama Islam Negeri Kendari, 2023)
The microfinance system is one of the governmental and non-governmental initiatives to eradicate poverty, even though conventional microfinance does not satisfactorily serve the needs of underprivileged households in Nigeria. However, Islamic microfinance has great potential to facilitate its roles in providing financial services per Islamic values. This research examines Islamic microfinance's perception of poverty eradication in the Kwara State of Nigeria. The 364 responses from microfinance clients in Ilorin, Kwara State of Nigeria, were analyzed through SPSS using descriptive and Pearson coefficient moment correlation (PPMC). The findings indicated a positive statistically significant correlation between Islamic microfinance and household income (PEHI), healthcare (PEHC), education(PEED), and employment(PEEM). This study is significant as it presents the applicability of Islamic microfinance for eradicating poverty in the study area. Policymakers should widely institutionalize Islamic microfinance institutions nationwide and take necessary and exclusive measures to ensure their effectiveness for poverty eradication and achieving sustainable socioeconomic development.